The PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL SUZUKI PADA PT. SEJAHTERA BUANA TRADA DI PEKANBARU: PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL SUZUKI PADA PT. SEJAHTERA BUANA TRADA DI PEKANBARU - Yulita, Rahma; Tinaria, Lisa (Jurnal Ekonomi dan Bisnis Indonesia, 2024)
This research aims to determine the influence of promotions and prices on the decision to purchase Suzuki cars at PT. Sejahtera Buana Trada in Pekanbaru The sample for this study was 85 people. The data analysis techniques used are quantitative and qualitative methods. The technical data used is multiple linear regression using SPSS 27. Based on the research results, it was found that the Promotion variable had a significant effect on the decision to purchase a Suzuki Car at PT Sejahtera Buana Trada in Pekanbaru. And price has a significant influence onthe decision to purchase a Suzuki car at PT. Sejahtera Buana Trada in Pekanbaru. There is a significant influence between promotion and price simultaneously or together on the decision to purchase a Suzuki car at PT. Sejahtera Buana Trada Pekanbaru. Keywords: Promotion, Price, Purchase Decision